Inheritance Pattern of Vocational Skills: An Ethno-Andragogic Study on Construction Workers in Indonesia - Widaningsih, Lilis; Barliana, Mohammad Syaom; Aryanti, Tutin; Malihah, & Elly (Journal of Technical Education and Training, 2018)
Construction workers in Indonesia have unique characteristics. They earn their vocational skills through cultural inheritance. Construction workers in many construction projects in urban areas mostly come from villages in Java. They learn their vocational skills from their relatives and local community in their village. This paper aims at describing how vocational skills are passed down through generations. This qualitative ethnographic and ethno-andragogic study explores the training process, beginning with the recruitment pattern, the network development, skills acquisition and transmission pattern, responses to technology, and attitudes to challenges in modern industry. Through observation and in-depth interview, it was revealed that traditionally the training pattern applied andragogic model principles; i.e., learning by doing and learning on the job.